2020
DOI: 10.1093/rheumatology/keaa326
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and granulomatosis with polyangiitis (GPA): a diagnostic challenge

Abstract: COVID-19 and granulomatosis with polyangiitis (GPA): a diagnostic challenge Rheumatology key message. Accurate diagnosis of COVID infection is especially important in those with comorbid lung conditions such as GPA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Clinicians are blindsighted by COVID-19, often missing conditions such as GPA. 4 Despite being in a pandemic, clinicians must have a broad differential diagnosis, especially when the clinical picture is not consistent with COVID-19. Our patient had normal oxygen saturation and downtrending inflammatory markers, yet her renal function continued to deteriorate with persistent haematuria and proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians are blindsighted by COVID-19, often missing conditions such as GPA. 4 Despite being in a pandemic, clinicians must have a broad differential diagnosis, especially when the clinical picture is not consistent with COVID-19. Our patient had normal oxygen saturation and downtrending inflammatory markers, yet her renal function continued to deteriorate with persistent haematuria and proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…However, initial diagnosis was challenging for two reasons: firstly, there were diagnostic algorithms implemented in response to the global pandemic to ensure appropriate levels of patient safety; secondly, the prodromal overlap and patient characteristics between ANCA-positive vasculitis and COVID-19 further complicated the diagnosis. 4,5 ANCA-positive vasculitides are the most common small-vessel vasculitides and include microscopic polyangiitis, eosinophilic granulomatosis with polyangiitis (Churg-Strauss Syndrome), and granulomatosis with polyangiitis (Wegener's granulomatosis). They are frequently missed or delayed in their diagnosis due to their nonspecific symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of the novel coronavirus disease (COVID-19) in Wuhan, China, towards the conclusion of 2019 has prompted inquiries into its pathogenesis, therapy, and clinical presentations across various health conditions (1). Previous research indicated that elderly individuals exhibited a heightened vulnerability to experiencing severe infection and consequences arising from COVID-19 (2). The reverse transcription polymerase chain reaction (RT-PCR) test is extensively employed as a diagnostic modality for COVID-19; nevertheless, it is associated with a notable incidence of false negative results.…”
Section: Introductionmentioning
confidence: 99%